1997
DOI: 10.1136/jnnp.63.3.351
|View full text |Cite
|
Sign up to set email alerts
|

Dural puncture and activated protein C resistance: risk factors for cerebral venous sinus thrombosis

Abstract: Objectives-Dural puncture is regarded a safe procedure when contraindications are carefully excluded and has so far not been recognised as a risk factor for cerebral venous sinus thrombosis (CVST). Five patients are described with CVST after dural puncture in the presence of additional risk factors. Methods-In four out of five patients complete investigations for thrombophilia were performed at least one month after withdrawal of oral anticoagulation. Results-In three out of four patients tested, activated pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
61
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 30 publications
2
61
0
2
Order By: Relevance
“…19 Also in 1997, another 4 patients with sinus thrombosis after dural puncture were described with either the FVL mutation or APC resistance. 20 Furthermore, 6 studies based on 12 to 40 patients with CVT found prevalences of FVL ranging from 10% to 25% [21][22][23][24][25][26] (Table 1). All patients with CVT described in these reports were heterozygous for the FVL mutation.…”
mentioning
confidence: 99%
“…19 Also in 1997, another 4 patients with sinus thrombosis after dural puncture were described with either the FVL mutation or APC resistance. 20 Furthermore, 6 studies based on 12 to 40 patients with CVT found prevalences of FVL ranging from 10% to 25% [21][22][23][24][25][26] (Table 1). All patients with CVT described in these reports were heterozygous for the FVL mutation.…”
mentioning
confidence: 99%
“…Similar reports of cerebral venous thrombosis complicating either dural puncture or idiopathic intracranial hypotension in nonobstetric patients highlight the rapid progression of postural headache to a severe non-postural headache [15][16][17][18]. It is hypothesised that traumatic damage to the fragile venous endothelial lining due to stretching of the cerebral vessels and relative stasis of blood flow in the vasodilated cerebral vasculature contribute towards thrombosis [15].…”
Section: Discussionmentioning
confidence: 67%
“…However, to our knowledge, only Miglis and Levine have previously reported a case of CVT following spinal surgery complicated by durotomy, which was treated with the aid of external CSF drainage, presenting a more dramatic outcome and a much shorter follow-up period [4]. Nevertheless, a few reports have associated CVT with other forms of spinal meningeal injury, including spontaneous intracranial hypotension, diagnostic lumbar puncture, myelography, and epidural and spinal anesthesia, as well as intrathecal administration of steroids and cytostatics [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The temporal gap between the iatrogenic injury to the spinal meninges and the diagnosis of CVT has ranged from a few hours to a few days.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the clinical presentation of CVT is nonspecific and isolated intracranial hypertension may be the sole manifestation of CVT, especially in patients with dural sinus thrombosis without involvement of superficial or deep veins [1][2][3]. CVT should be excluded every time in patients with symptoms of intracranial CSF hypotension after spinal surgery and/or external lumbar CSF drainage show the following: (1) complaint of headache that worsens after an initial plateau, loses its orthostatic character or lasts for more than a few days after the introduction of proper treatment; and (2) a decreased level of consciousness, encephalic focal neurologic deficits or seizures [4,5,20,23]. However, the change in headache pattern may not reliably predict the development of CVT [20].…”
Section: Discussionmentioning
confidence: 99%